Analysis of the State Procurement Law and its regulations - Tapia Orejón, María Isabel Magaly (2014)
Objective: Determine the legal limitations of the Procurement Law of the State and its Rules of Procedure adopted by the Legislative Decree N° 1017 prevent the participation of the MYPES District of Tacna in state procurement. Methods: Once you have reviewed the theory, information provided in the Procurement Law of the State and its Regulation has been confronted with the reality the MYPES 373 microentrepreneurs. It has formulated a series of questions according to the indicators, variables, to determine the incidence of the MYPES in state procurement. For this purpose has been considered the application of the questionnaire and documentary analysis, which was applied to the given sample size, it is proceeded to the tabulation, processing, the results were analyzed and interpreted both descriptive and statistically. Results: After the phase of analysis and interpretation of results, a comparison was made between employers Micro and requiring certain requirements in the State Contracting Law by charts and graphs. Conclusions: We obtained the 13.23 % level of participation of the micro and small entrepreneurs in the state purchases, represents legal barrier to their participation in state purchases: The guarantee of seriousness of Offer (access to financing through the banking system), the enforceability of the requirements and payments for the processing of the RNP (National Register of Suppliers) and the deadlines for payments represent a legal barrier to their participation in state procurement in the Government Contracts Law and its Rules of Procedure adopted by the Legislative Decree N° 1017.